2017
DOI: 10.1080/08958378.2016.1267282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titanium dioxide nanoparticles (TiO2 NPs) on the expression of mucin genes in human airway epithelial cells

Abstract: These results demonstrate for the first time that TiO NPs induce MUC5B expression via TLR4-dependent ERK1/2 and p38 MAPK signaling pathways in respiratory epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Recently, Kim et al reported an in vitro experiment regarding the expression of mucin genes in human airway epithelial cells. The authors confirmed that TiO 2 -NP initiated the TLR4-dependent pathway, leading to the MUC5B overproduction, which relates to the inflammatory response in human airway [37]. In Suarez-Lopez del Amo et al experiment, the TiO 2 particles derived following implantation were collected and co-cultured with the oral epithelial cells (NOK-SI).…”
Section: Resultsmentioning
confidence: 93%
“…Recently, Kim et al reported an in vitro experiment regarding the expression of mucin genes in human airway epithelial cells. The authors confirmed that TiO 2 -NP initiated the TLR4-dependent pathway, leading to the MUC5B overproduction, which relates to the inflammatory response in human airway [37]. In Suarez-Lopez del Amo et al experiment, the TiO 2 particles derived following implantation were collected and co-cultured with the oral epithelial cells (NOK-SI).…”
Section: Resultsmentioning
confidence: 93%
“…The major macromolecular component of mucus is mucin. 9 Among the 14 human mucoid genes identified to date, mucin 5AC (MUC5AC) encodes the major mucin core protein secreted from the airway surface epithelium. 10 MUC5AC is highly expressed in the lung and its expression was up-regulated by various bacterial stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…in vitro exposure of bronchial (E. Y. Chen et al, 2011;Kim et al, 2017) and colonic (Dorier et al, 2019) epithelial cell lines to TiO 2 NP stimulated an increase in mucus production. We found a similar increase following a single, high dose of oral TiO 2 NPs in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Studies with human bronchial epithelial cells have shown an increase in mucus production in response to TiO 2 (E. Y. Chen et al, 2011;Kim, Choi, Bae, Song, & Kim, 2017); therefore, we predicted the expression of the main secreted mucin, muc2, would be affected by TiO 2 NP treatment. At 24 hours post-gavage, muc2 expression was lower in TiO 2 NP-treated animals compared with controls ( Figure 3).…”
Section: Mucin-2 Expression Elevated In Cecum Postexposurementioning
confidence: 99%